Analysis of the Effectiveness the use of Closed-Circuit Television (CCTV) for Control of Road Code Crime - Cardoso, Moises; Gusmao, Fernando Dias; Martins , Leoneto Madeira (International Journal Labs, 2025)
The capital Dili of east Timor is currently undergoing rapid changes for urban development toward more modern and globalized city. With the increasing urban population, Dili has become one of the most crowded cities in east Timor prone to conflict and violence. With The growth of urban population and the limited access to public transports force many people infavor of private transportation for their daily activities. However, most of the people using private transportations such as; motorbikes, cars and many other vehicles are often lacked the knowledge and understanding of the health and safety related issues when using their vehicle. Although the relevant institutions and traffic police regularly campaigned and socialiasing the health and safety precaution when using and operating any types of vehicles. However, with the installation of CCTV(Closed Circuit Television)technology have given traffic police the opportunity to develop traffic control managenement effectively and prevent accidents through CCTV surveillance. The installation of CCTV not only monitoring and recording traffic activities on the roads, but it’s enabling the police and local authority to monitor and analyze the situation in public areas such as; shopping mall, city centre, parking area, public park. The installation of CCTV program in the context of social order, with the aims were to maintaining public safety and security, reduce crime and emergency response. Hence, the CCTV is widely arguably the most effective toolfor law enforcement officers or security officials to maintain social order and prevent crime and criminality. The major theories used to analyze the results of this research are social control theory, strategy theory and effectiveness theory. Aspects of control, strategy and effectiveness become measures for the researcher to analyze and interpret the use of CCTV to supervise vehicles that use public roads in the city of Dili related to the existing road code. The descriptive qualitative method is a natural and holistic approach to explore, understand, and explain complex phenomena from the perspective of individuals or groups. Data collection process through observation, interview and documentation. All data collected will be analyzed using the Milles and Huberman interactive model and Swot Analysis. The basic result of this research is that the CCTV installed by the National Police on the public roads in the capital Dili is in a good condition in terms of camera and image capture. Most public roads, especially the main road in Dili, have installed CCTV. However, there are some public roads that have not been installed. In fact, only two cases (accident and incident) have used CCTV as evidence. Ineffectiveness in managing the use of CCTV to control violation cases due to lack of resources such as facilities, personnel skills and the number of personnel who conduct CCTV monitoring. The cost of paying telecommunications operators is high, but its use for control is more cases whose volume per day is small (accidents and incidents) than cases of infringement that per day CCTV accept many.